Juan Soldado : rapist, murderer, martyr, saint - Vanderwood, Paul J. (American encounters/global interactions., 2004)
Paul J. Vanderwood offers a fascinating look at the events, beliefs, and circumstances that have motivated popular devotion to Juan Soldado, a Mexican folk saint. In his mortal incarnation, Juan Soldado was Juan Castillo Morales, a twenty-four year old soldier convicted of and quickly executed for the brutal rape and murder of eight year old Olga Camacho in Tijuana in 1938. Immediately after Morales's death, many people began to doubt the evidence of his guilt, or at least the justice of his brutal execution. There were reports of seeing blood seeping from his grave and of hearing his soul cry out protesting his innocence. Soon the "martyred" Morales was known as Juan Soldado, or John the Soldier. Believing that those who have died unjustly sit closest to God, people began visiting Morales's grave asking for favours. Within months of his death, the young soldier had become a popular saint. He is not recognized by the Catholic Church, yet since 1938, thousands of people have made pilgrimages to his gravesite. While Juan Soldado is well known in Tijuana, southern California's Mexican American community, and beyond, this book is the first to situate his story within a broader exploration of how and why such popular canonizations take root and flourish. In addition to extensive archival research, Vanderwood interviewed central actors in the events of 1938, including Olga Camacho's mother, citizens who participated in the riots demanding Morales's release to a lynch mob, those who witnessed his execution, and some of the earliest believers in his miraculous powers. Vanderwood also interviewed many present-day visitors to the shrine at Morales's grave. He describes them, their petitions-for favours such as health, a good marriage, or safe passage into the U.S.-and how they reconcile their belief in Juan Soldado with their Catholicism. Vanderwood puts the events of 1938 within the context of Depression-era Tijuana and he locates people's devotion, then and now, within the history of extra-institutional religious activity. In Juan Soldado, a gripping true-crime mystery opens up into a much larger and more elusive mystery of faith and belief